The hardware design and implementation for CAVLC and Exp-Golomb in H.264/AVC - Jing Chen; Yongliang Chen; Hantao Zhu; Chunchun Sui; PuFeng Wu; Xixin Cao (2010 The 12th International Conference on Advanced Communication Technology (ICACT), 2010)
Context-based adaptive variable-length coding (CAVLC) is a new and important feature of the latest video coding standard H.264/AVC. Together with Exp-Golomb(which is also called UVLC), CAVLC is used to code source data, i.e., quantized transformed coefficients (QTCs), and header data, respectively. In this paper, a hardware architecture for CAVLC and Exp- Golomb in the H.264/AVC codec is proposed, the main concept is the three-stage block pipelining scheme for this architecture. The simulation results show that our CAVLC and Exp-Golomb system can run at 31.2 MHz and 156.6 MHz clock frequency respectively.